THE POSSIBILITY OF THE PHILLIPED CLASSROOM MODEL IN HIGHER EDUCATION - Sarvinoz NORMAMATOVA (Scholar Express Journal, 2024)
This article presents scientific recommendations for the use of flipped classroom technology in the organization of educational processes of students studying in higher education institutions.
Keywords: Information technologies; blended learning; independent education